Knowledge, attitudes and preventive practices towards soil-transmitted helminthiases among teachers in schools implementing the home-grown school feeding program in Enugu Metropolis, Enugu State, Nigeria - Daniel Chukwuemeka Obi; Blessing Hafizetu Nwazulu; Susan Chioma Udeh (BMC Public Health)
Abstract Background Soil-transmitted helminthiases (STHs) are prevalent in low- and middle-income countries, impacting school-aged children significantly. Teachers, integral to STH control through the Home-Grown School Feeding Program (HGSFP), need adequate knowledge, attitudes, and preventive practices (KAP) for successful STH prevention. However, there is limited research on teacher KAP regarding STH in Enugu State, particularly concerning its endemic nature. This study assessed the KAP of primary school teachers involved in the HGSFP in Enugu Metropolis, Nigeria, aiming to inform targeted interventions for STH control. Methods This analytical cross-sectional study, conducted from September 2023 to January 2024, involved 108 primary school teachers from nine randomly selected schools in Enugu Metropolis, Nigeria. Data were collected using a structured questionnaire, which had undergone rigorous validation and reliability testing. Descriptive statistics, chi-square tests, and logistic regression analyses were performed. Results While 69.4% of the teachers demonstrated good knowledge and 77.8% had good attitudes towards STH, only 27.8% reported good preventive practices. Younger teachers (25–34 years) exhibited better knowledge (94.1% vs. 56.4%, p = 0.018) and practices (52.9% vs. 30.8%, p = 0.015) compared to their older colleagues (≥ 45 years). Years of teaching experience significantly influenced attitudes, with teachers having 11–20 years of experience exhibiting the most favorable attitudes (95.8%, p = 0.030). Age was a significant predictor of good practice with teachers aged 35–44 years being 7.72 times more likely to report good practices than those ≥ 45 years (AOR: 7.72, 95% CI: 5.66–35.9). Conclusions The study reveals a critical disconnect between high levels of knowledge and positive attitudes towards STH among teachers and their lower levels of good preventive practices. This highlights that positive attitudes alone may not be sufficient for effective implementation of preventive measures. This underscores the need for targeted interventions, particularly tailored training for older and more experienced teachers. Incorporating evidence-based behavior change strategies, addressing potential barriers to practice implementation, and improving access to resources are crucial for enhancing STH prevention efforts within the HGSFP and safeguarding the health of teachers and students.